Faktor-Faktor Yang Menentukan Keberhasilan Produk Melalui Desain Logo Pada Produk Og Home Care - Sahtriando Sijabat; Tiarmi Arta Indah; Fikri Ramadhan; Atika Ramadhani Pulungan; Sandi Hiskia Hasibuan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
OC Home Care Soap is one of the products whose sales are offline and online at an affordable price. The more soap products that appear, it is required to be more creative in creating products with that made a logo design so that it becomes a trigger thing that will be seen by many people. Logo design not only displays the product's brand, but the logo design also presents the message or information of the product. In running a business, questions always arise about the importance of a logo for product success, this is what research will do. This research method uses the Google form feature to create a questionnaire which is then given to related parties.